Simpson index and food security: The case study of Kalimantan - Murjani, Ahmadi; Wiratama, Budhi Fatanza (Jurnal Ekonomi Indonesia, 2025)
Dietary diversity is a reliable indicator of food security. This study examines diversity in consumption through the Simpson Index using the food expenditure approach at the regency and city levels in Indonesia, with a particular focus on Kalimantan, the location of the new capital city, Nusantara. Further analysis explores the relationship between dietary diversity and food inflation, a key aspect of food security. The data used to develop the index is drawn from the National Socio-Economic Survey (SUSENAS) conducted by Statistics Indonesia from 2020 to 2023. Food inflation modeling was performed using the Threshold Panel Regression method on data from 90 cities. The findings suggest that concerted efforts are required to enhance food diversity in the supporting regions around IKN, particularly in South Kalimantan, which exhibits a relatively lower Simpson Index compared to other areas in Kalimantan. Moreover, the Simpson Index achievement has a significant impact on reducing food inflation rates, indicating its potential as a tool for monitoring and evaluating food price fluctuations, which are critical for maintaining economic access to national food security.